2010
DOI: 10.3109/10929088.2010.525025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CT slice thickness on accuracy of implant positioning in navigated total hip arthroplasty

Abstract: There are many published reports demonstrating the accuracy of CT-based navigation systems. However, the use of such systems often subjects patients to a high level of radiation exposure. CT scans acquired using thinner slices are considered to lead to more accurate results, but also increase radiation exposure. We took the postoperative CT scans for 56 cases of total hip arthroplasty performed using a CT-based navigation system and analyzed the accuracy of the cup and stem positioning. Of these cases, 41 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several studies have investigated the accuracy of measurements obtained using a goniometer or navigation systems during THA [12][13][14][15][16] (Table 4). They reported that the mean absolute measurement accuracy ranged from 4.5°-7.3°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the accuracy of measurements obtained using a goniometer or navigation systems during THA [12][13][14][15][16] (Table 4). They reported that the mean absolute measurement accuracy ranged from 4.5°-7.3°.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the optimal positions for the acetabular components, and the accuracy of acetabular component positioning using free-hand techniques, mechanically guided techniques, or navigation systems have also been investigated [8][9][10][11]. Other studies have examined the accuracy of intraoperative measurements of stem anteversion obtained using a goniometer or navigation systems during THA [12][13][14][15][16]. However, only one CTbased navigation study has reported the accuracy of stem positioning during THA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although a few reports described clinical accuracy or measurement error in CT-based navigation systems with regard to both cups and stems, they commonly showed that results for stems were not better than those for cups. [18,29] Kitada et al [18] evaluated anatomic orientation of cup and stem anteversion in THA with a CT-based navigation system, just as we did. They reported that the navigation system produced a measurement error of 0.4 ± 2.5 (range, À6 to 5 ) for cup inclination, À0.8 ± 4.1 (range, À6 to 8 ) for cup anteversion, and -0.6 ± 4.8 (range, -11 to 10 ) for stem anteversion, which is noteworthy because cup inclination and anteversion in anatomic notation are larger than those in radiographic notation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another group of investigators revealed that the clinical accuracy of stem anteversion was worse than that of cup anteversion in THA with same navigation system. [29] They investigated the influence of the thickness of CT slices, but they found no effect on stem anteversion when slices were between 1 and 3 mm thick.…”
Section: Discussionmentioning
confidence: 99%
“…3 mechanically guided techniques, or navigation systems have also been investigated [8][9][10][11]. Other studies have examined the accuracy of intraoperative measurements of stem anteversion obtained using a goniometer or navigation systems during THA [12][13][14][15][16]. However, only one CT-based navigation study has reported the accuracy of stem positioning during THA [17].…”
mentioning
confidence: 99%